If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 1 + -2v + 5 Reorder the terms: 6 = 1 + 5 + -2v Combine like terms: 1 + 5 = 6 6 = 6 + -2v Add '-6' to each side of the equation. 6 + -6 = 6 + -6 + -2v Combine like terms: 6 + -6 = 0 0 = 6 + -6 + -2v Combine like terms: 6 + -6 = 0 0 = 0 + -2v 0 = -2v Solving 0 = -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. 0 + 2v = -2v + 2v Remove the zero: 2v = -2v + 2v Combine like terms: -2v + 2v = 0 2v = 0 Divide each side by '2'. v = 0 Simplifying v = 0
| 6y+3=6y-8 | | -13x-15=-54 | | -3(5-x)-(x-2)=7x-2 | | 11d+9d=20 | | 12=3u+72 | | 3z^3+7z^2+27z+63=0 | | 12x+12=10x-10 | | 0.86=In(y) | | 3/7x-4=12 | | 3/7x-4=16 | | 3x+18x^2-81x=0 | | -4(x-1)=10x-10 | | 4x-14/x-3 | | Y=80-2x | | 4v+28=v+51 | | 3x+7=7x+13 | | 3tgx+4=tgx+4 | | 18/x-3=6 | | 2x^2+6=166 | | 15x^2-2=123 | | 2w=10w-32 | | 7x-11=5x-15 | | 90=-6+2(-4x+10) | | 0=2x^2-6x+24 | | V+8=-3 | | h(t)=-5t^2+80t+3 | | 7x+9=-3y | | 5x^2-2=123 | | 15-10*4= | | 3x+7+3y-1=180 | | ×/4=3.6 | | -2b+3b=19 |